The African elephant offered to Henry IV by sailors of Dieppe (1591) - (:unkn) unknown (My University, 2018)
The arrival in Dieppe of an elephant offered as a gift to King Henry IV is the subject, in 1893, of a short note edited by Léopold Delisle. The discovery of new sources invites a reinterpretation of this extraordinary event since it is probably the first African elephant introduced in Europe by the Atlantic route since Ancient history.The shipping of a young 5-year-old pachyderm during several weeks requires particularly elaborate logistics : the carriers must prevent the animal from getting scared or ill, they must also insure that it is getting the water and food necessary for its growth and maintenance. The resort to an experienced African healer is unavoidable. The transportation of the elephant from Cape Verde is a remarkable achievement, at the same time technical, commercial and most assuredly diplomatic, thus revealing the great knowledge that the sailors of Dieppe had of the African coasts.
Keywords: African Research